Pengaruh Kombinasi Dua Aditif Terhadap Penundaan Waktu Pemadatan Pada Beton - Puluhulawa, Indriyani; Idham, Muhammad (Journal of Applied Civil Engineering and Infrastructure Technology, 2025)
The decrease in a slump due to the long distance between the batching plant and the casting site is a common issue. This also increases the likelihood of reducing concrete quality due to delays in compaction. To reduce the risks of slump loss and decrease concrete compressive strength, a combination of two admixtures was employed: Sika Plastocrete RT6 Plus, acting as a retarder, and Grolen Hp19R, serving as a superplasticizer. The dosages applied were 0.3% for Sika Plastocrete RT6 Plus and 0.4% for Grolen Hp19R. Compaction delays were tested at 0, 60, 90, and 120-minute intervals. The results demonstrated that combining these two admixtures could enhance the concrete's setting time, slump, and compressive strength compared to normal concrete. However, with the increasing delay in compaction time, there was a noted decrease in the concrete's slump and compressive strength.